Efficiency of Private Sector Credit on the Economy of Nepal - Koirala, Sujan (Economic Review of Nepal, 2025)
This paper attempts to analyze the impact of domestic credit to private sector on economic growth of Nepal. Based on the time series data covering the time period from 1975 to 2022, the study has employed the ratio of private credit to domestic credit as a main independent variable and real gross fixed capital formation, ratio of remittance to GDP, the ratio of export to GDP, real gross value added on transportation and communication and real exchange rate have been used as control variables, while real GDP has been used as a proxy of economic growth. Employing Engle Granger two step procedure, the result of the study revealed that domestic credit to private sector is found instrumental in both short run and long run in influencing the economic growth of Nepal. Hence, the study recommends that appropriate monetary policy measures are desirable for enhancing the productive capacity and thereby by economic growth.